2001
DOI: 10.1046/j.1365-2265.2001.01275.x
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and quality of life in adults with growth hormone deficiency; effects of low‐dose growth hormone replacement

Abstract: Low-dose GHR improves body composition and QoL as early as 1 month after commencement and the beneficial effects continue at 3 months. Most importantly, these changes occur in the absence of side-effects. We therefore suggest the use of low-dose GH therapy, maintaining IGF-I between the median and upper end of the age-related reference range, for the treatment of AGHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 43 publications
2
28
1
1
Order By: Relevance
“…QOL was assessed by a variety of non-specific and disease-specific questionnaires in this study. In contrast to findings in several previous controlled and open-label studies (3,47,48), we were unable to demonstrate significant improvements in QOL. Several explanations are possible.…”
Section: Discussioncontrasting
confidence: 56%
“…QOL was assessed by a variety of non-specific and disease-specific questionnaires in this study. In contrast to findings in several previous controlled and open-label studies (3,47,48), we were unable to demonstrate significant improvements in QOL. Several explanations are possible.…”
Section: Discussioncontrasting
confidence: 56%
“…Fat mass is one of the most responsive external markers of the effects of GH in patients with GHD. Nevertheless, no relationship between changes in QoL and changes in fat mass, lean body mass, or IGF-I has been found in a variety of studies (11,18,19), except one which reported a significant correlation between body composition change as determined by bioelectrical impedance analysis and change in QoL score as measured with the disease-specific questionnaire, Quality of LifeAssessment of GHD in Adults (QoL-AGHDA) (20). Here, using DXA, we found significant associations between changes in general health and physical functioning subscales and fat mass change, with the trend being more consistent in AO than CO patients.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, gender differences in the doses required to normalise IGF1 levels have indeed been noted in subgroup analyses, with females receiving a higher GH replacement dose than males in some studies (28,35), although some have found no significant differences in GH dose needed between men and women (22,45) when dose adjustments are made for baseline factors such as age, BMI, and dose of GH itself (46). Differences in the response to GH, as reflected by changes in body composition, have been observed, with several studies demonstrating greater effects in males than in females.…”
Section: Gendermentioning
confidence: 99%
“…Results suggested that 12 months of lowdose GH therapy normalised bone metabolism and cortical bone density, and improved trabecular bone density without causing adverse events. The effects of low-dose GH replacement on body composition and QoL were studied by Ahmad et al (22). A starting daily dose of 0.4-0.5 IU (0.13-0.17 mg) that was titrated to achieve and maintain IGF1 SDS between the median and upper end of the age-related reference range (mean GH dose of 0.77G0.08 IU at 1 month and 0.80 G0.12 IU at 3 months) was associated with an improvement in body composition and QoL.…”
Section: Weight-based Vs Individualised Regimensmentioning
confidence: 99%